Brainstem evoked response auditory in healthy term neonates with hyperbilirubinemia - Isman Jafar; Irawan Mangunatmadja; Rinawati Rohsiswatmo; Sudjatmiko Sudjatmiko; Ronny Suwento; Safarina G. Malik (Paediatrica Indonesiana, 2010)
Background Bilirubin in healthy term neonates, especially freeÂ bilirubin (Bf), could enter brain cell and cause damage perceivedÂ by brainstem evoked response auditory (BERA). Studies identifyÂ that Bf is more associated to abnonnal BERA than total bilirubinÂ is. Currently, phototherapy is perfonned in neonates with totalÂ bilirubin > 15 mg/dL. However, in developing countries whereÂ observation could not be done optimally, neonates \\lith totalbilirubin> 12 mg/dL will be subject for phototherapy.Objectives To determine the association between total bilirubinÂ > 12 mg/dL and BERA abnonnalities in healthy tenn neonates,Â and the value of total bilirubin and free bilirubin that initiateÂ abnonnal BERA.Methods This cross sectional study was carried out between MarchÂ 31ô€…August 8, 2008, in healthy term neonates at roomingô€…in ward,Â Department of Obstetric & Gy necology, Cipto MangunkusumoÂ Hospital (CMH). All eligible subjects were examined for Bf andÂ BERA using standard methods.Â Results The prevalence of abnormal BERA was 15.4%. ThereÂ was no significant relation between hy perbilirubinemia (> 12 mg/Â dL) and abnonnal BERA in healthy tenn neonates. Lowest totalÂ bilirubin and Bf level related to abnonnal BERA were 12.4 mg/dLÂ (mean 12.8 mg/dL) and O.oS)Lg/dL (mean l.3)Lg/dL), respectively.Â All BERA abnonnalities were unilateral.Conclusions There is no association between abnormal BERAÂ and hyperbilirubinemia (total bilirubin> 12 mg/dL) in jaundicedÂ infants who undergo phototherapy.